The Growth Stop Phenomenon Of Baobabs (Adansonia Spp.) Identified By Radiocarbon Dating. Issue 2 (28th December 2016) - Patrut, Adrian; Woodborne, Stephan; von Reden, Karl F; Hall, Grant; Patrut, Roxana T; Rakosy, Laszlo; Danthu, Pascal; Pock-Tsy, Jean-Michel Leong; Lowy, Daniel A; Margineanu, Dragos
Abstract: The article reports the growth stop phenomenon, which was documented only for baobabs, i.e. for trees belonging to the Adansonia genus. The identification of growth stop was enabled by radiocarbon dating, which allows a complex investigation of samples collected from the trunk/stems of baobabs. In several cases, the outermost rings of baobabs, which were close to the bark, were found to be old, with ages of several hundreds of years, instead of being very young. Dating results of samples collected from six baobabs are presented. For multistemmed baobabs, the growth stop may occur only for one or several stems. We identified four factors that may induce the growth stop: (i) stress determined by severe climate conditions, (ii) old age, (iii) the need to keep a stable internal architecture, and (iv) the collapse of stems that survive this trauma. Baobabs and their stems affected by growth stop may survive for several centuries, by continuing to produce leaves, flowers, and fruits. This phenomenon was associated with the capacity of baobabs to store large amounts of water in their trunks/stems in the rainy season. This reservoir of water is used during the dry season and allows the trees to survive prolonged drought periods.